Ensaio clínico randomizado, duplo-cego, controlado por placebo sobre o efeito do frutooligossacarídeo na constipação intestinal em lactentes - Souza, Daniela da Silva [UNIFESP] (2016)
Objective: To assess the prevalence of constipation and its relation with the type of feeding and food intake among infants. Methods: 568 infants were assessed. Constipation was characterized by the elimination of hard stools associated with one of the following: painful or difficulty defecation, lumpy, cylindrical shape with cracks or thick cylindrical shape stools and frequency of bowel movements < 3 times per week. Type of feeding was classified in breastfeeding plus complementary feeding, mixed breastfeeding and artificial feeding. A pediatric feeding questionnaire was used to assess food intake. Results: Constipation was observed in 18.0% (n=102) of the infants. Breastfeeding plus complementary feeding was more frequent among the infants without constipation, however it was not statistical significant (p=0,116). In 75.4% of the infants who mixed fed and artificial fed the substitute for breast milk was cow?s milk. The intake of main baby food twice a day was more frequent among the infants without constipation, yet the difference was not statistical significant (p=0,062). The intake of greens, vegetables and beans (p=0,424; p=0,413; p=0,621, respectively) was similar in the infants with or without constipation, however the intake of fruits was lower among the infants without constipation (p=0,004). Conclusion: Intestinal constipation was not related to type of suckling. The intake of greens, vegetables, and beans was similar in infants with and without intestinal constipation, however, the intake of fruits was higher among the infants without constipation. The intake of main baby food twice a day may be associated with lesser occurence of constipation.